PENGARUH CERITA BUDAYA BIMA UNTUK MENINGKATKAN KETERAMPILAN STORYTELLING PADA PELAJARAN BAHASA INDONESIA KELAS IV DI SDN INPRES KAMBILO - Putri Irma Suryani; Nunung Fatimah; Ayub Qadhafi Saputra (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This ponder points to examine the impact of using Bima cultural folktales on improving storytelling skills among fourth-grade students at SDN Inpres Kambilo. The research was motivated by the students' low speaking ability in delivering stories coherently and expressively. The study applied a quantitative approach with a one-group pretest-posttest design involving 12 students as participants. Instruments included expert material validation questionnaires, teacher and student observations, and storytelling performance tests. The material validity reached a